Major Phenolics in Yerba Mate Extracts (Ilex paraguariensis) and Their Contribution to the Total Antioxidant Capacity - Deladino, Lorena (2013)
Yerba mate (Ilex paraguariensis) is an indigenous crop which is highly consumed as an infusion in the South American subtropical forest. It has a high concentration of antioxidant substances, providing health benefits and helping to prevent diseases. The objectives of this work were to characterize an aqueous yerba mate extract by spectrophotometric and chromatographic (HPLC) methods and to study the effect of the freeze-drying process on the polyphenols profile and antioxidant activity, determined by a novel method. An aqueous extract was obtained and lyophilized to obtain a yerba mate powder with antioxidant properties. The extracts showed a high polyphenol content, determined by Folin-Ciocalteau and HPLC, and a high antioxidant activity towards the DPPH· radical and after the recently developed method of photochemiluminescence. A linear correlation was found between Folin-Ciocalteau and DPPH methods for lyophilized samples. HPLC analysis allowed determining antioxidant components like rutin, caffeine and chlorogenic acid. Lyophilization caused a decrease in total polyphenol content and antiradical activity of the extracts and this fact was mainly attributed to changes in the chlorogenic acid related compounds and rutin structures, after their photochemiluminescence data. The photoluminiscent method proves to be an advantageous approach for antioxidant capacity determination.